(3bhGYO GdCMcGe aj eYQaI GdMdGd hGdMQGes - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s ((3CMeO Hf eMeO GdTQjas)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg Ydi ShGHZ GdfYeGA hJQGOa GdBdGA GdeJaVd HEQSGA GdCfHjGA dEQTGO GdOgeGA CeG HYO agPG cJGH bhGYO GdCMcGe aj eYQaI GdMdGd hGdMQGe ELGHI dGdJeGS CMH GdfGS Edj hCYRge Ydj hgh GdhdO GdYRjR eMeO s
(3BNQgG (B:s
(3aCceg hCUdM eG JLOg ef GdNdd hGdfbUGf hGdNWC hGdfSjGf gPg hUjJj Edjc hGddg NdjaJj Ydjc s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 227s
(3eYLe GdeDdajf (B1 / 598s
(3EjVGM Gdecfhf (B2 / 242s
(3CYjGf GdTjYI (B24 / 277s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis